Place of Hiding - George, Elizabeth (New York, N.Y. : Bantam Books, 2003)
In A Place of Hiding, bestselling novelist Elizabeth George marks new territory in the darker landscapes of human relationships. She tells a gripping, suspenseful story of betrayal and devotion, war and remembrance, love and loss...and the higher truths to which we must all ultimately answer.
82305
Keywords: Murder -- Fiction; Betrayal -- Fiction; Guernsey (Channel Islands) -- Fiction